High Energy Injury Ankle Fracture-Dislocation without Neurovascular Involvement - Utomo, Pamudji; Arimuqti, Zarkasyi; Santoso, Asep; Sibarani, Tangkas SMHS; Anwar, Iwan Budiwan (Indonesian Journal of Medicine, 2020)
Background: Open tibiotalar joint dislocation associated with medial malleolus and distal fibular fracture without neurovascular damage are rarely reported.Case presentation: This study present a case of 55-year-old female with open tibiotalar joint dislocation associated with medial malleolus and distal fibular fracture without neurovascular injury treated with emergent debridement, open reduction, and internal fixation.Results: Six months follow-up showed complete bone and soft tissue healing with excellent functional outcome.Conclusion: Emergent debridement, open reduction, and internal fixation is needed to treat tibiotalar joint dislocation associated with medial malleolus and distal fibular fracture.Keywords: high energy injury, ankle joint, fracture dislocationCorrespondence: Asep Santoso. Department of Orthopaedic and Traumatology, Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: asepsantoso@gmail.com.Indonesian Journal of Medicine (2020), 05(03): 259-264https://doi.org/10.26911/theijmed.2020.05.03.12